Improved method for vibration control of the technical condition of a power transformer based on fractal analysis of the amplitude-time characteristics - V. R. Basenko; I. V. Ivshin; O. V. Vladimirov; M. F. Nizamiev (Известия высших учебных заведений: Проблемы энергетики, 2023)
The purpose of this work is to improve the method of vibration control of a power transformer through the use offractal analysis of the amplitude-time signal.   Fractal analysis of the amplitude-time characteristics will allow to quantify the degree of «indentation» of the vibration signal of the transformer associated with a defect. For a quantitative assessment, the fractal analysis coefficient (FAC) was introduced based on the determination of the fractal dimension by the Hausdorff-Besikovich method. To test the developed method, a non-contact laser measuring and diagnostic complex (LCMC) with developed software based on LabVIEW, ImageJ and Python was used. Experimental studies of the transformer TSZ 16 were carried out using the developed method and LCIK. The CFA of the windings and magnetic circuit of the transformer under study, the level of technical condition for the controlled elements of the transformer are determined.   METHODS. The improved method of control makes it possible to increase the accuracy of control of a power transformer during its operation under voltage, which makes it possible to switch from a planned system of transformer repairs to a system for taking repairs according to the current technical condition.   RESULTS. The improved method of vibration control was tested using the developed non contact LCIK, the level of technical condition of the power transformer under voltage was determined.   CONCLUSION. An improved method of vibration control makes it possible to determine the level of technical condition of an energized power transformer with the possibility of automatically obtaining a decision on the technical condition, as well as to use statistical methods for processing and analyzing the signals received from the transformer.